2016
DOI: 10.1017/s0950268816002958
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the benefits of ART and PrEP in resource-limited settings

Abstract: SUMMARY Antiretroviral therapy (ART) is increasingly being used as an HIV-prevention tool, administered to uninfected people with ongoing HIV exposure as pre-exposure prophylaxis (PrEP) and to infected people to reduce their infectiousness. We used a modelling approach to determine the optimal population-level combination of ART and PrEP allocations required in South Africa to maximize programme effectiveness for four outcome measures: new infections, infection-years, death and cost. We considered two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…These studies span from 2007 to 2017 with 42 studies modelling oral PrEP in sub‐Saharan Africa and two studies with non‐specific settings but of relevance for generalized HIV epidemics. Applications of country‐specific modelling of oral PrEP occurred predominantly for South Africa and Kenya , followed by Botswana , Zambia , and one application each for Zimbabwe , Mozambique , Nigeria , and Uganda . Select country‐specific results were additionally presented in two studies .…”
Section: Resultsmentioning
confidence: 99%
“…These studies span from 2007 to 2017 with 42 studies modelling oral PrEP in sub‐Saharan Africa and two studies with non‐specific settings but of relevance for generalized HIV epidemics. Applications of country‐specific modelling of oral PrEP occurred predominantly for South Africa and Kenya , followed by Botswana , Zambia , and one application each for Zimbabwe , Mozambique , Nigeria , and Uganda . Select country‐specific results were additionally presented in two studies .…”
Section: Resultsmentioning
confidence: 99%
“…This cost data was collected in 2003 and published in 2006. While the importance of the paper as one of very few sources of ART cost data in the early years of the public-sector ART programme cannot be overstated, it was still used as a cost source for papers published as recently as 2016 [4749]- at which stage the data used in the models was over 10 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from different parts of the world showed that PrEP, especially when used concomitantly with other interventions, was highly effective in reducing new HIV diagnoses and in fact achieved the most rapid decrease (15)(16)(17)(18).…”
Section: Clinical and Research Consequencesmentioning
confidence: 99%